Rare occurrence of adenocarcinoma in an endocervical polyp: diagnostic and clinical challenges - Gupta, Sumedha; Chadha, Saloni; Kalwaniya, Dheer Singh; Dhir, Bhawuk (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Endocervical polyps, typically benign, are frequently discovered during routine gynecological examinations, although they may present with abnormal uterine bleeding or increased vaginal discharge. Malignant transformation within these polyps is rare, with an estimated incidence ranging from 0.0% to 1.7%. We present a case of a 38-year-old premenopausal woman who exhibited secondary infertility and abnormal uterine bleeding, eventually diagnosed with invasive adenocarcinoma within an endocervical polyp. Diagnostic evaluations including histopathology and imaging confirmed deep infiltrating endometriosis and uterine adenomyosis. Following multidisciplinary consultation, the patient underwent a cone biopsy, which revealed chronic cervicitis. Ultimately, a hysterectomy with bilateral salpingo-oophorectomy was performed. The final histopathology revealed leiomyoma and endometriosis, with no malignancy beyond the polyp. This case highlights the diagnostic challenges associated with malignancies within cervical polyps and underscores the importance of excising and thoroughly examining such polyps, even when cytological findings are negative.